2010
DOI: 10.2151/sola.2010-035
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Stratospheric Sudden Warming Event on Tropical Clouds and Moisture Fields in the TTL: A Case Study

Abstract: The impact of stratospheric sudden warming event in September 2007 on the tropics was investigated based on satellite data (CALIOP, MLS and TRMM PR). Equatorial temperature and water vapor at 100 hPa decreased by about 1 K and 1 ppmv within 10 days, respectively. Changes in tropical clouds are observed together with the occurrence of the SSW as i) frequent formation of higher-level cirrus clouds over the Maritime Continent, to where water vapor was transported from Asian Monsoon and where the lowest temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
(18 reference statements)
2
26
1
Order By: Relevance
“…In the troposphere, upwelling develops near 5°S and downwelling develops near 15°N, indicating a southward shift of the upward branch of the Hadley circulation. Development of similar structures during SSW events has been noted by observational studies (Eguchi and Kodera 2010;Kodera et al 2011).…”
Section: A General Circulation Model Study Of the Impact Of A Stratossupporting
confidence: 66%
See 1 more Smart Citation
“…In the troposphere, upwelling develops near 5°S and downwelling develops near 15°N, indicating a southward shift of the upward branch of the Hadley circulation. Development of similar structures during SSW events has been noted by observational studies (Eguchi and Kodera 2010;Kodera et al 2011).…”
Section: A General Circulation Model Study Of the Impact Of A Stratossupporting
confidence: 66%
“…These circulation changes are induced by amplified planetary wave forcings (Dunkerton et al 1981;Garcia 1987;Randel 1993). Recent studies have suggested that the impact of SSW events penetrates still further downward in the tropics, by modulating convective activity in the tropical troposphere (Kodera 2006;Eguchi and Kodera 2010;Kuroda 2008). However, tropical convection can influence the stratospheric circulation through modification of the extratropical planetary waves (Taguchi and Hartmann 2006), or tropical planetary waves (Norton 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is known that the frequency of SSWs is influenced by the direction of the stratospheric quasi-biennial oscillation (QBO) of the zonal wind in the tropics (e.g., Holton and Tan, 1980): SSWs are more frequently observed if the zonal wind in the tropics at 50 hPa is westward. However, there are also indications for influences in the opposite direction: SSWs can influence the tropospheric temperature and convection in the tropics (e.g., Kodera, 2006), and thereby also tropical clouds and moisture (Eguchi and Kodera, 2010). In particular, SSWs have strong influence on the composition of the stratosphere by modulating the tropical ascent of trace species into the stratosphere (Tao et al, 2015a, b).…”
Section: Relevance Of Ssws For Global Modelingmentioning
confidence: 99%
“…Stratospheric temperature decreases, but minimal temperature changes occur in the TTL, resulting in a decrease in static stability in the upper TTL (Li and Thompson, 2013). In the regions where deep convective clouds are frequent, stratospheric influence further penetrates deeper in the troposphere (Eguchi and Kodera, 2010;Kodera et al, 2011b). Once the distribution of convective clouds is modified, this effect can be amplified within the troposphere through a feedback involving water vapour transport (Eguchi and Kodera, 2007).…”
Section: Introductionmentioning
confidence: 99%